Geoeconomic fragmentation, globalization, and multilateralism - Anni Norring (Bank of Finland, 2024)
The world is witnessing growing turbulence stemming from geopolitics and a tangible threat of economic disintegration. There are some indications of globalization in retreat, international trade growth slowing down and a transition from optimizing efficiency of global value chains towards ensuring their resilience. Disentangling the causes and effects of the various trends around global economic integration and pushing towards de-globalization is extremely difficult. This paper aims to inform the policy debate and the research agenda by giving an overarching view of geoeconomic fragmentation, i.e., economic disintegration driven by geopolitics. It defines the relevant concepts, channels of effect and amplification mechanisms, and discusses the main causes and implications of geoeconomic fragmentation.
urn:nbn:fi-fe2024031811700
Keywords: E61; F02; F10; F13; F15; F20; F30; F42; F60; 330; geoeconomic fragmentation; globalization; international monetary system; global financial safety net; multilateralism; costs of economic fragmentation